Prejudice, Identity, and Social Acceptance in Z-O-M-B-I-E-S (2018): A Critical Film Analysis - Aura Wida Rofahima; Nurmalia Gemor (TEKILA: Journal of Language Teaching and Literature, 2026)
This study aims to critically analyze the representation of prejudice, identity, and social acceptance in the Disney film Z-O-M-B-I-E-S (2018), directed by Paul Hoen. Although the film is widely recognized for its entertaining and educational value, there is still limited analytical research that explores how these social themes are constructed through characters and symbolic elements. This study employs a qualitative descriptive approach, focusing on character development, narrative conflict, and symbolism. The findings show that prejudice is portrayed as a systemic issue embedded in social structures, particularly through the segregation between humans and zombies in Seabrook. Identity is reflected in the transformation of the main characters, Addison and Zed, who challenge social expectations and redefine their roles within society. Social acceptance is depicted as a gradual process achieved through interaction, empathy, and the breakdown of stereotypes. In addition, symbolic elements such as the Z-Band represent social control and discrimination, while visual differences function as markers of otherness. The study concludes that Z-O-M-B-I-E-S presents a simplified but meaningful representation of complex social issues. It highlights the importance of tolerance, inclusivity, and respect for diversity, making the film relevant as both a cultural text and an educational resource.